Pengembangan Kurikulum Pembelajaran Bahasa Arab di Rumah Tahfidz Al-Hidayah Yogyakarta - Agni, Dagi Mardhan Agae; Hermawan, Hermawan (ARZUSIN, 2024)
This research is titled “Arabic Learning Curriculum Development at Rumah Tahfidz Al-Hidayah Yogyakarta”, which aims to formulate, design, and evaluate the Arabic learning curriculum to the needs of Tahfidz students. The focus of this research is to develop a curriculum that supports the ability of students in Arabic, especially to strengthen memorization and understanding of the Quran. The research method used is Research and Development (R&D) with a development model consisting of several stages: needs analysis, product design, expert validation, and revision. The results showed that the current Arabic curriculum at Rumah Tahfidz Al-Hidayah Yogyakarta still has limitations in terms of the instability of the curriculum used and does not support students' understanding of what they memorize. The curriculum design developed is based on Language Learning for Specific Purposes, which emphasizes language skills that are contextual to the lives of students as Quran memorizers. This curriculum involves all four language skills: listening, speaking, reading, and writing, and applies active learning methods to increase Santri's involvement in the learning process. Curriculum validation was carried out by experts in the field of Arabic curriculum and experts in the field of tahfidz, the results showed that this curriculum design was feasible and by the needs of the students of Rumah Tahfidz Al-Hidayah. Some input from the experts was implemented to improve this curriculum, especially in terms of material selection.